2014
DOI: 10.1016/j.neuropharm.2014.04.015
|View full text |Cite
|
Sign up to set email alerts
|

Glutamatergic mechanisms associated with stress-induced amygdala excitability and anxiety-related behavior

Abstract: The neural factors underlying individual differences in susceptibility to chronic stress remain poorly understood. Preclinical studies demonstrate that mouse strains vary greatly in anxiety-related responses to chronic stress in a manner paralleled by differential stress-induced changes in glutamatergic signaling in the basolateral amygdala (BLA). Previous work has also shown that alterations in the amygdala gene expression of the GluN1 NMDA and the GluK1 kainate receptors are associated with stress-induced al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
41
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 44 publications
(62 reference statements)
4
41
0
1
Order By: Relevance
“…For instance, increased excitatory responses to glutamate and increased glutamatergic synaptic transmission. The increased excitatory response to glutamate could be caused by increased neuronal membrane excitability (Rosenkranz et al, 2010;Hetzel and Rosenkranz, 2014), increased function of NMDA or AMPA receptors (Adamec et al, 2005;Caudal et al, 2010;Mozhui et al, 2010;Suvrathan et al, 2014), reduced glutamatergic drive of GABAergic networks (Masneuf et al, 2014), or upregulation of glutamatergic receptors (Lei and Tejani-Butt, 2010;Gan et al, 2014). Increased glutamatergic synaptic transmission could be caused by increased glutamatergic inputs, as observed here and in other studies (Mitra et al, 2005;Vyas et al, 2006;Padival et al, 2013Padival et al, , 2015Suvrathan et al, 2014;Tsai et al, 2014).…”
Section: Discussionsupporting
confidence: 71%
“…For instance, increased excitatory responses to glutamate and increased glutamatergic synaptic transmission. The increased excitatory response to glutamate could be caused by increased neuronal membrane excitability (Rosenkranz et al, 2010;Hetzel and Rosenkranz, 2014), increased function of NMDA or AMPA receptors (Adamec et al, 2005;Caudal et al, 2010;Mozhui et al, 2010;Suvrathan et al, 2014), reduced glutamatergic drive of GABAergic networks (Masneuf et al, 2014), or upregulation of glutamatergic receptors (Lei and Tejani-Butt, 2010;Gan et al, 2014). Increased glutamatergic synaptic transmission could be caused by increased glutamatergic inputs, as observed here and in other studies (Mitra et al, 2005;Vyas et al, 2006;Padival et al, 2013Padival et al, , 2015Suvrathan et al, 2014;Tsai et al, 2014).…”
Section: Discussionsupporting
confidence: 71%
“…Recent animal work emphasizes an involvement of NMDAR-dependent signalling in medial prefrontal cortex (mPFC) and amygdala during emotional processing and emotion-cognition interactions, including emotional learning (Vieira et al, 2015;Hegoburu et al, 2014;Masneuf et al, 2014). These are in line with studies in humans which revealed emotion-specific disruptions during facial emotion encoding and recognition, as well as altered amygdala and prefrontal functioning following ketamine-induced NMDAR blockade (Ebert et al, 2012;Schmidt et al, 2013, Abel et al, 2003.…”
Section: Introductionsupporting
confidence: 55%
“…The results of a number of studies performed in recent years indicate that glutamatergic neurotransmission Simvastatin → Farnesyl Pyrophosphate ↓ → H-Ras ↓ → NMDA receptor ↑ via ionotropic receptors is involved in the pathophysiology of anxiety (Masneuf et al, 2014). The ionotropic glutamate receptor family comprises ligand-gated channels divided into three groups named after their selective agonists, namely NMDA, AMPA, and kainate and their density is high in cortical and limbic regions implicated in the mediation of fear and anxiety (Bergink, van Megen, Westenberg, 2004;Réus et al, 2015).…”
Section: Involvement Of the Nmda Receptor Complex In Anxiolytic-like mentioning
confidence: 99%
“…Modulation of NMDA receptors activity after SIM treatment could explain the drug's anxiolytic-like effects (Camargo et al, 2013;Carrocini et al, 2012;Cruz et al, 2011;Kilic et al, 2012;Pauleti et al, 2013;Santos et al, 2012;Wang et al, 2009;Yan et al, 2011). This hypothesis could be supported by the fact that altered levels of NMDA receptors in the hippocampus and amygdala directly influence anxiety behaviors (Barkus et al, 2010;Blundell, Adamec, 2007;Masneuf et al, 2014).…”
Section: Introductionmentioning
confidence: 98%